Standarisasi Resep Rendang Daging Di Lubuk Alung Kabupaten Padang Pariaman - Wiwik Gusnita; Ira Mariana (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
This research aims to produce a Standard recipe and quality beef rendang. This type of research is qualitative and quantitative research using mixed method. The research was conducted in the city of Lubuk Alung in March 2020. Data source There are two namely: a qualitative data source is taken from people who are good at making meat rendang, quantitative data sources are obtained from 5 limited panelists. Qualitative data collection techniques are observations, interviews, documentation and quantitative data collection techniques are prganoleptic test poll formats. Qualitative data analysis techniques using three threads of activity are: data reduction, data presentation, drawing conclusions and quantitative data analysis techniques using formulas (Mx = ∑ x/N), the validity of qualitative data validity test data namely: extension Observational, diligent observation, and tringulation. Based on the results of the research obtained Rendang meat recipes include materials used, the number of ingredients, how to make, and the quality of Rendang meat. From this beef Rendang recipe that is used as a standardized beef Rendang recipe that has been converted. Standardized beef Rendang recipe conducted organoleptic test to quality to get the good quality of beef Rendang include: The form of Beef rendang (square), color (blackish brown), aroma (fragrant), texture (soft), and flavor (savory).